2007
DOI: 10.1111/j.1460-9568.2007.05435.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor activity is modulated via different neuronal circuits in rats with chronic liver failure than in normal rats

Abstract: The mechanisms by which liver failure alters motor function remain unclear. It has been suggested that liver disease alters the neuronal circuit between basal ganglia and cortex that modulates motor function. Activation of group I metabotropic glutamate receptors in the nucleus accumbens (NAcc) by injecting (S)-3,5-dihydroxyphenylglycine (DHPG) activates this circuit and induces locomotion We analysed by in vivo brain microdialysis the function of the circuits that modulate motor function in rats with liver fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…It is described that animals that are subjected to this surgical model of type C HE develops liver failure, jaundice, portal hypertension, bacterial translocation, immune system dysfunction, hyperammonemia and low-grade encephalopathy [21]. Using this animal model we have obtained evidence that the biosynthetic machinery for transmitter GABA is disturbed [23], which may be of interest since GABAergic neurotransmission has been related to aberrations in the behavioral parameters that are normally associated with HE [12], [24].…”
Section: Introductionmentioning
confidence: 99%
“…It is described that animals that are subjected to this surgical model of type C HE develops liver failure, jaundice, portal hypertension, bacterial translocation, immune system dysfunction, hyperammonemia and low-grade encephalopathy [21]. Using this animal model we have obtained evidence that the biosynthetic machinery for transmitter GABA is disturbed [23], which may be of interest since GABAergic neurotransmission has been related to aberrations in the behavioral parameters that are normally associated with HE [12], [24].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most frequently used is the portacaval shunt model, considered one of the best models of chronic minimal type B HE, 4 which corresponds to encephalopathy associated with a portosystemic shunt. Although portacaval-shunted rats have been found to experience difficulties when learning tasks, including passive and active avoidance and conditional discrimination tasks in the Y maze, [5][6][7] little research has focused on the learning deficits of these animals in the Morris water maze (MWM). [8][9][10] The goal of the present work was to evaluate spatial reversal learning in a rat model of portacaval anastomosis and to study the oxidative metabolism of various brain limbic system regions involved in memory via histochemical labeling of cytochrome oxidase (CO).…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicate that in control rats, DHPG induces locomotion by activating the normal neuronal circuit: NAcc --> VP --> MDT --> PFCx and in PCS rats this circuit is not activated but DHPG injection in PCS rats activates an alternative circuit: NAcc --> SNr --> VMT --> PFCx that is not activated in control rats. These experiments suggest that dopamine increase i n d u c e d b y D H P G w o u l d a c t i v a t e t h e n o r m a l n e u r o n a l c i r c u i t , w h i l e a n i n c r e a s e i n glutamate would activate the alternative circuit (Cauli et al, 2007).…”
Section: Microdialysismentioning
confidence: 81%
“…Cauli et al (2007) demonstrated that the function of the circuits that modulate motor function in rats with liver failure due to portacaval shunt (PCS) is dependent on the kind of neurotransmission. They found this result by analyzing the function of the circuits that modulate motor function in rats with liver failure due to portacaval shunt (PCS) using in vivo brain microdialysis.…”
Section: Microdialysismentioning
confidence: 99%